Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Does any body know a expansion of : $\cos^k(\theta)$ in function of $\cos$ and/or $\sin$ but without power? For example : $\cos^2(\theta)=\frac{1}{2}(\cos(2\theta)+1)$, but i would want a generalization to the power $k$. I searched in Abramowitz and Stegun but didn't find anything !

share|cite|improve this question
Just write $\cos \theta = \frac12 (e^{i\theta} + e^{-i\theta})$ and expand using the binomial theorem... – Hans Lundmark Mar 6 '12 at 13:41
Surely there is a better word for this than "development". – Alex Becker Mar 6 '12 at 13:45
which word should I use? – PanAkry Mar 6 '12 at 14:10
"Expansion" is better. – Hans Lundmark Mar 7 '12 at 10:10

$$ \cos^k \theta = \left( \frac{ e^{i\theta} + e^{-i\theta} }{2} \right)^k = \frac{1}{2^k} \sum_{n=0}^k \binom{k}{n} (e^{i\theta} )^n (e^{-i\theta})^{k-n} = \frac{1}{2^{k+1} } \sum_{n=0}^k 2\binom{k}{n} e^{i(2n-k)\theta} $$

Since $ \binom{k}{n} = \binom{k}{k-n} $ we split up the sum and reverse the index of summation in the second term as follows:

$$ = \frac{1}{2^{k+1} } \left( \sum_{n=0}^k \binom{k}{n} e^{i(2n-k)\theta} + \sum_{n=0}^k \binom{k}{k-n} e^{i(2n-k)\theta}\right) = \frac{1}{2^{k+1} } \left( \sum_{n=0}^k \binom{k}{n} e^{i(2n-k)\theta} + \sum_{n=0}^k \binom{k}{n} e^{i(k-2n)\theta}\right) $$

$$ = \frac{1}{ 2^{k} } \sum_{n=0}^k \binom{k}{n} \left( \frac{ e^{i(2n-k)\theta} + e^{-i(2n-k)\theta} }{2} \right) =\frac{1}{ 2^{k} } \sum_{n=0}^k \binom{k}{n} \cos ( (2n-k)\theta). $$

share|cite|improve this answer
of course I didn't try this way. Thanks – PanAkry Mar 6 '12 at 13:58

I just wish to contribute a "quicker" development of Ragib Zaman's derivation. Just as he had shown, $$ \cos^k \theta = \left( \frac{ e^{i\theta} + e^{-i\theta} }{2} \right)^k = \frac{1}{2^k} \sum_{n=0}^k \binom{k}{n} (e^{i\theta} )^n (e^{-i\theta})^{k-n} = \frac{1}{2^k } \sum_{n=0}^k \binom{k}{n} e^{i(2n-k)\theta} $$ Now, assuming that $\theta$ is real, we know that $\cos \theta \in \mathbb{R}$, so both sides of the above equation must be real. Thus, we may take the real part on both sides with no change on the left hand side, i.e. $$ \cos^k \theta = \text{Re} \left [ \frac{1}{2^k } \sum_{n=0}^k \binom{k}{n} e^{i(2n-k)\theta} \right ] = \frac{1}{2^k } \sum_{n=0}^k \binom{k}{n}\;\, \text{Re} \left [ e^{i(2n-k)\theta} \right ], $$ whereby $$ \cos^k \theta = \frac{1}{2^k } \sum_{n=0}^k \binom{k}{n}\;\, \cos \left[ (2n - k) \theta \right ] $$

share|cite|improve this answer

The example you give can be generalized using trigonometric identities. For odd $k$ we get $$\cos^k(\theta)=2^{1-k}\sum\limits_{n=0}^{\frac{k-1}{2}}\binom{k}{n}\cos((k-2n)\theta)$$ while for even $k$ the formula becomes $$\cos^k(\theta)=2^{-k}\binom{k}{\frac{k}{2}}+2^{1-k}\sum\limits_{n=0}^{\frac{k}{2}-1}\binom{k}{n}\cos((k-2n)\theta).$$

share|cite|improve this answer

You can repeatedly replace powers of the cosine by a combination of smaller powers and $\cos(n\theta)$ using Chebyshev polynomials of the first kind. I'm not sure the resulting coefficients have any conventional name, though.

Alternatively, express $\cos x$ as a Fourier series and use the second convolution theorem to raise it to the $k$th power.

share|cite|improve this answer
thank you! maybe it will be useful later for me. – PanAkry Mar 6 '12 at 13:59

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.